Pengaruh Tingkat Pendidikan, Pengalaman Kerja dan Pengetahuan Akuntansi terhadap Penyusunan Laporan Keuangan UMKM Berdasarkan SAK EMKM pada Pelaku UMKM Kuliner (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the influence of education level, work experience, and accounting knowledge on the preparation of financial reports in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in culinary MSMEs. This study uses a quantitative approach with primary data collection through interviews and questionnaires. The study population consists of culinary MSMEs registered with the Medan City Cooperatives and MSMEs Office, with a focus on Medan Perjuangan and Helvetia Districts. The sample was selected using a purposive sampling technique, with predetermined criteria. Data analysis was carried out using multiple linear regression methods analyzed using SPSS Statistics software version 29.00. The results of the study indicate that simultaneously, education level, work experience, and accounting knowledge have a positive and significant influence on financial reporting in accordance with SAK EMKM in culinary MSMEs. This indicates that the higher the level of education, work experience, and accounting knowledge, the greater the likelihood of culinary MSMEs to prepare financial reports in accordance with the established standards. This research provides an important contribution for culinary MSMEs in improving the quality of their financial management, particularly in the preparation of accurate financial reports in accordance with the provisions of the EMKM SAK, which in turn can improve their performance and competitiveness in the market. In addition, the results of this study are expected to serve as a basis for related parties, such as the government and educational institutions, in designing more effective training and coaching programs, to improve the accounting competency of MSME actors, and encourage them to be more compliant in preparing financial reports in accordance with applicable standards.